2019
DOI: 10.5935/2359-4802.20190049
|View full text |Cite
|
Sign up to set email alerts
|

Association between Insulin use and Infective Endocarditis: An Observational Study

Abstract: Background: The association between Diabetes Mellitus (DM) and Infective Endocarditis (IE) is controversial in the literature, since many controversial results have been published. However, when evaluating specifically the evidence on IE and individuals with DM using insulin, we found only two observational studies that considered this variable, with discordant results regarding the prognosis and prevalence of Staphylococcus sp in insulin users compared to non-users. Despite the lack of evidence, in clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One study comprised 2 reports, but both were included since one reported data on clinical and imaging characteristics (Casabe et al, 1996b) and the other reported data on microorganisms and further clinical manifestations (Casabe et al, 1996a). We treated this study as one throughout the review leading to 44 studies(Allende González et al, 2020;Avellana et al, 2018;Bahamondes et al, 2008;Bezerra et al, 2020;Burgos et al, 2019;Casabe et al, 1996b;Corral et al, 1993;Cremona et al, 2007;Damasco et al, 2014;Ediap et al, 2017;Ferreiros et al, 2006;Flores et al, 2017;Fragomeni et al, 2003;Fránquiz Cuéllar and Alvarez Ozambela, 1986;Holanda et al, 2015;Jacob Filho et al, 1988;Jáuregui Camargo et al, 1997;Kaiser et al, 1984;Leyva Quert et al, 2009;Marino et al, 2014;Merello et al, 2019;Monteiro et al, 2017;Murdoch et al, 2009;Negrín Expósito et al, 2003;Nieto et al, 1985;Olaya-Sanchez et al, 2019;de Oliveira et al, 2018;Ortiz et al, 1983;Oyonarte G et al, 2003;Pérez Zerpa et al, 2020;Pinheiro et al, 2018;Pivatto Júnior et al, 2020;Popilovsky et al, 2014;Ris et al, 2019;Romero Flecha and Aveiro Figueredo, 2020;Saito et al, 2014;Siciliano et al, 2014a…”
Section: Study Selectionmentioning
confidence: 99%
“…One study comprised 2 reports, but both were included since one reported data on clinical and imaging characteristics (Casabe et al, 1996b) and the other reported data on microorganisms and further clinical manifestations (Casabe et al, 1996a). We treated this study as one throughout the review leading to 44 studies(Allende González et al, 2020;Avellana et al, 2018;Bahamondes et al, 2008;Bezerra et al, 2020;Burgos et al, 2019;Casabe et al, 1996b;Corral et al, 1993;Cremona et al, 2007;Damasco et al, 2014;Ediap et al, 2017;Ferreiros et al, 2006;Flores et al, 2017;Fragomeni et al, 2003;Fránquiz Cuéllar and Alvarez Ozambela, 1986;Holanda et al, 2015;Jacob Filho et al, 1988;Jáuregui Camargo et al, 1997;Kaiser et al, 1984;Leyva Quert et al, 2009;Marino et al, 2014;Merello et al, 2019;Monteiro et al, 2017;Murdoch et al, 2009;Negrín Expósito et al, 2003;Nieto et al, 1985;Olaya-Sanchez et al, 2019;de Oliveira et al, 2018;Ortiz et al, 1983;Oyonarte G et al, 2003;Pérez Zerpa et al, 2020;Pinheiro et al, 2018;Pivatto Júnior et al, 2020;Popilovsky et al, 2014;Ris et al, 2019;Romero Flecha and Aveiro Figueredo, 2020;Saito et al, 2014;Siciliano et al, 2014a…”
Section: Study Selectionmentioning
confidence: 99%
“…The sample consisted of 211 patients, whose profile has been described in a previous study: 8 110 from Belo Horizonte and 101 from Ipatinga. Their median age was 48.0 (33-59) years and 70.6% were men.…”
Section: Resultsmentioning
confidence: 99%
“…The menisci are fibrocartilaginous structures that provide important functionalities to the biomechanical complex of the knee, such as axial and tension forces, cushioning, synovial fluid distribution and an increase in articular surface area between the tibia and femur. [1][2][3][4] These structures are attached to the knee by meniscocapsular ligaments, which contain meniscofemoral and meniscotibial (MTL) components. 1,5,6 Peltier et al 7 described the importance of MTLs for knee stability, especially for posteromedial rotation stability.…”
Section: Introductionmentioning
confidence: 99%